Mosses for minimalist green roofs: A preliminary study of the effects of rooftop exposure, species selection, and lab-grown vs. wild-harvested propagule sources - Sean R. Haughian; Jeremy L. Lundholm (Nature-Based Solutions, 2024)
Mosses are rarely explicitly included in urban green infrastructure projects in much of North America. Nevertheless, their opportunistic colonization of impervious surfaces in the absence of intervention, combined with successful tests of their suitability in other parts of the world, suggests that they may be suited to expanded use in applications such as green roofs, and beneficial to urban ecosystem services. Such inclusion requires more detailed knowledge of both general methods for incorporating mosses into green infrastructure, and species-specific knowledge on propagation methods and maximizing growth. In this report, we present a 3-year green roof trial with five types of moss replicated across both wild and lab grown inocula, on both sheltered and exposed asphalt roof surfaces in Atlantic Canada. The exposed roof surface was not conducive to bryophyte survival; repeated wind damage, combined with rapid onset of chlorosis from drought stress, resulted in a complete mortality of all species in that condition. In the sheltered habitat, all species were still present by the third year, but with much lower cover than was present post-installation. In general, wild-harvested shoots survived better than lab-cultivated ones, and those mosses transplanted from shady habitats fared better than those from sunny habitats. We conclude that surface attachment and degree of exposure are the most important factors for establishing moss growth on asphalt roofs, whereas selecting among species may be important only in the context of maximizing long-term growth under highly localized conditions, such as high litter deposition or partial vs. full shade from overhead trees.